2018
DOI: 10.5812/aapm.69322
|View full text |Cite
|
Sign up to set email alerts
|

Normal Reference Interval of WBC Count After On - Pump Coronary Artery Bypass Graft; When Values Could Be Misleading

Abstract: BackgroundApplying the cardiopulmonary pump produces inflammatory responses and induces leukocytosis. White Blood Cell (WBC) count has a diagnostic value for detecting different infections. In this study, we want to redefine the normal value reference intervals of WBC count in Coronary Artery Bypass Graft (CABG) patients, to prevent misdiagnose leukocytosis as a sign of infection.MethodsIn an observational study, 140 patients who underwent on - pump CABG were enrolled to find out normal values of the reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…It increases in the first 24 hours and decreases after 48 hours. 16 Postoperation WBC reference intervals are higher than the WBC normal ranges. 16 A pretreatment with lidocaine mitigated endotoxininduced increases in polymorphonuclear granulocytes (PMN) adherence, PMN activation, migration to the inflammatory site, and metabolic function, assessed by an inhibition of free radical production.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It increases in the first 24 hours and decreases after 48 hours. 16 Postoperation WBC reference intervals are higher than the WBC normal ranges. 16 A pretreatment with lidocaine mitigated endotoxininduced increases in polymorphonuclear granulocytes (PMN) adherence, PMN activation, migration to the inflammatory site, and metabolic function, assessed by an inhibition of free radical production.…”
Section: Discussionmentioning
confidence: 87%
“…16 Postoperation WBC reference intervals are higher than the WBC normal ranges. 16 A pretreatment with lidocaine mitigated endotoxininduced increases in polymorphonuclear granulocytes (PMN) adherence, PMN activation, migration to the inflammatory site, and metabolic function, assessed by an inhibition of free radical production. 17 Nishina et al 18 reported that pre-or early posttreatment with lidocaine attenuates the late phase of acid installation-induced lung injury in rabbits.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For years, glomerular filtration rate calculations have included race as a variable of consideration, but this practice has recently been re‐examined to determine its utility 65 . In addition, normal white blood cell count reference intervals are continuously being discussed in the context of patient variables, with one example showing an increased reference range following coronary artery bypass 67 . These two examples show how the definition of normality in biologic measurements is fluid and continuously changing as new information on variables affecting them develops, and this is certainly no different with TEWL as shown in this review.…”
Section: Major Open Questionsmentioning
confidence: 99%